The Sony Playstation! : consumer marketing the world's most popular interactive entertainment home console : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Media Studies at Massey University, Palmerston North, New Zealand - Tung, Raymond (Massey University, 2001)
The focus of this thesis is the marketing methods used for the Sony PlayStation. Marketing in the video game industry has been ignored by a number of theorists, who tend to concentrate on the influences and effects of video games on children and youth. There are two research methods used. The first is textual analysis of selected video games, in terms of the availability of related marketing material. The individual marketing techniques used by Sony for each game are outlined and discussed. The second research method used is qualitative research via questionnaires on the marketing of PlayStation games. Respondents were asked a number of questions about marketing techniques used by Sony. This method was used to gain information from the most important factor in marketing, the consumer. The results from the questionnaires and case studies revealed that communication strategy and pricing strategy were the most important features in marketing the PlayStation. The advertising for PlayStation games promotes and informs the consumer and the price of games is an important factor for the purchaser. As with every promotion or advertisement, the trademark logo of the Sony PlayStation are visible in television ads, magazines, store displays and posters. The logos and brand trademarks provide Sony with a business image that can be identified. Essentially, Sony have used different forms of media technology to market their products to the consumer. The content and material from a number of PlayStation promotions is ambiguous. Sony are prepared to create advertisements where consumers are expected to make the connection between the content within the advertisement and what is actually being promoted.
The videocassette may be viewed in the library.
Keywords: Electronic games industry; Case studies Marketing; Sony video games